CHALLENGES AND SOLUTIONS TO INCREASE YOUTH PARTICIPATION IN RELIGIOUS ACTIVITIES - S. Adam, Muh. Wahyuddin; Abdulrahman, Anisa; Nawawi, Natasya; Hulopi, Friskilan; Djingo, Sri Meliyanti; Kurniawati, Astrid (SYAHADAT: Journal of Islamic Studies, 2024)
In modern usage, the word "adolescence" or adolescence comes from the Latin word "adolescence", which means "to grow up" or "to grow into adulthood". The broader meaning of this term includes mental, emotional, social, and physical maturity. Piaget supports this idea by stating that "adolescence is an age at which individuals become integrated into adult society, an age at which they do not feel that they are below the level of older people but feel the same, or at least equal to older people". In simple terms, religion is belief. Based on the KBBI, belief can be interpreted as a control system for believing in and worshiping spiritual beings as well as rules relating to human life and the environment. Human relationships with God and each other are regulated by a system of beliefs and customs known as religion. Based on the research findings above regarding problems and solutions to increase youth participation in religious activities, there are many challenges faced by teenagers today in participating in religious activities in their surrounding environment. Therefore, researchers can conclude that to overcome this problem, material providers must deliver material in a way that is more innovative and relevant to teenagers' daily lives. Apart from that, schools and the community must help by providing supportive facilities. It is hoped that collaboration between mosques, schools and communities can create a positive environment that encourages teenagers to participate in religious activities.